2015
DOI: 10.1097/mco.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 polyunsaturated fatty acids and brain aging

Abstract: These recent human and experimental studies provide support for and clarification of how ω-3 PUFA protect against brain aging and highlight the main lines for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 47 publications
0
37
0
2
Order By: Relevance
“…n-3 PUFA are one the major components of neuronal membranes and key modulators of neuroinflammation, oxidative stress, and neurogenesis [16,17]. They include eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), docosapentaenoic acid (DPA) and alpha-linolenic acid (ALA) [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…n-3 PUFA are one the major components of neuronal membranes and key modulators of neuroinflammation, oxidative stress, and neurogenesis [16,17]. They include eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), docosapentaenoic acid (DPA) and alpha-linolenic acid (ALA) [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…DHA in particular is uniquely accumulated in central nervous system tissue and its presence beneficially J Physiol 594.16 impacts upon plasma membrane function, synaptic transmission and cellular signalling (Yehuda et al 1999). In vitro studies have also revealed a number of neuroprotective properties of DHA and EPA that may improve brain health including attenuation of inflammatory responses by either suppressing pro-inflammatory pathways and upregulating pro-resolving mediators such as neuroprotectin D1, or modulating mitochondrial function and reducing oxidative stress (Denis et al 2015). There is also evidence from animal and human studies to suggest that dietary supplementation with omega-3 PUFAs improves regional CBF, which may contribute to the preservation of both brain structure and function (Tsukada et al 2000;Jackson et al 2012).…”
Section: Dietmentioning
confidence: 99%
“…The increasing evidences support the beneficial effect of an increased intake of omega-3 fatty acids (omega-3FA) in a variety of neurodegenerative and neurological conditions [17] . The dietary sources of omega-3FA are fish and sea foods, which are rich sources of DHA.…”
Section: Introductionmentioning
confidence: 97%